Further Extension of a Theorem of Values Distribution of Meromorphic Function $f^{(k)}f^n$ (Communications in Mathematical Research, 2021)
In this paper we derive the fundamental inequality of the theorem of meromorphic functions. It extends some results of Yi Hong-xun et al. As one of its applications, we then study the value distribution of $f^{(k)} f^n - c(z)$.
Keywords: transcendental meromorphic function; small function; value distribution.